The dose-response relationship between socioeconomic deprivation and alcohol-attributable mortality risk - a systematic review and meta-analysis - Probst, Charlotte; Lange, Shannon; Kilian, Carolin; Saul, Celine; Rehm, Jürgen (BMC medicine, 2021)
Individuals with low socioeconomic status (SES) experience a higher risk of mortality, in general, and alcohol-attributable mortality in particular. However, a knowledge gap exists concerning the dose-response relationships between the level of socioeconomic deprivation and the alcohol-attributable mortality risk.